Fermentation kinetics of some oil palm by-products as ruminant feeds. - Wong, Siew Pung; Rajion, Mohamed Ali; Goh, Yong Meng; M., Ebrahimi (2011)
The ruminant industry in Malaysia is still not self-sufficient where smallholder farmers keep the majority of ruminant livestock. Limited pasture and poor quality forages urge them to find alternative feedstuffs which are cheaper, of satisfactory nutritive value and available throughout the year. Oil palm by-products meet these criteria, however their fermentation kinetics in the rumen need to be evaluated. The in vitro fermentation kinetics of selected oil palm by-products, namely the oil palm fronds (OPF), palm kernel cake (PKC) and decanter cake (DC) were evaluated using the in vitro gas production technique. The by-products were assessed at inclusion levels of 100% (raw 100% by-product), 15% (15% by-product + 85% concentrate feed, w/w) and 30% (30% by-product + 70% concentration feed, w/w). The in vitro fermentation of the oil palm by-products was carried out in 100 mL sealed syringes with 0.25 g of substrateand 25 mL of rumen fluid-buffer mixture (1:4 v/v), which were incubated at 39ºC under anaerobic condition for 48 h. Evaluation of the fermentation kinetics was performed on the following parameters, namely gas production, rumen pH, protozoal population, volatile fatty acid (VFA) and long chain fatty acid (LCFA) profiles compared with concentrate feed which acted as the control. The decanter cake (DC) at inclusion levels of 15% and 30% yielded similar gas production, rumen pH, VFA, and total unsaturated fatty acid profile as the concentrate feed. However, the 15% and 30% DC significantly increased the total C18:1 trans fatty acids (p<0.05) compared to the concentrate and the other by-products. It is concluded that the decanter cake showed the greatest potential to be included into ruminant livestock feed which should reduce feed costs, although the increase in the unhealthy trans fatty acids must be taken into account.